Photodegradation Behavior of Agricultural Antibiotic Oxytetracycline in Water - Lee, Youn Jun; Lee, Jong Min; Lee, Chang Gu; Park, Seong Jik; Jho, Eun Hea (Water (Switzerland), 2022)
Due to their overuse in agriculture, antibiotics are discharged into the aquatic environment, which poses a threat to human health and aquatic organisms. The agricultural antibiotic oxytetracycline (OTC) persists in aquatic media for a long time due to its resistance to biological degradation. Photolysis is a main pathway for its degradation in the natural environment and wastewater treatment, and thus, the photolysis of OTC should be investigated. In this study, the effects of reaction conditions such as the irradiation conditions, the initial OTC concentration, and the water matrix on OTC photolysis were investigated. The most efficient degradation was observed when UV-C was used as the irradiation source (k = 0.0148 ± 0.0008 min−1), and the removal ratio increased with higher light intensity. A lower initial OTC concentration and higher solution temperature were advantageous for the degradation of OTC. The presence of humic acid or inorganic ions negatively affected the degradation rate of OTC. In addition to the effects of the reaction conditions, the degradation kinetics of OTC in actual agricultural water and the photolysis of various antibiotics such as streptomycin, validamycin A, and oxolinic acid were further studied. This work proved that various factors could decrease the photodegradation of OTC, which raises the potential risks that are associated with the persistent use of antibiotics in the water environment. Therefore, the results of the present study can help to provide an understanding of the effects of various reaction conditions on the degradation of agricultural antibiotics.
Keywords: Actual agricultural water; Agricultural antibiotics; Agricultural water; Aquatic environments; Aquatic media; Coexisting ion; Human health; Oxytetracycline; Photo degradation; Reaction conditions; actual agricultural water; agricultural antibiotics; coexisting ions; oxytetracycline; photodegradation